Criminal Execution of Fines Against the Criminal Actors of Sales of Goods Without Signs of Exchange Refund - Ika Mutiara Putri (Ius Poenale, 2020)
Criminal penal subsidair imprisonment imposed by the panel of judges used as a gap that is used by the convicted person to be free from the obligation to pay fines. Besides that, there are obstacles for the prosecutor to implement the execution of criminal fines, because the criminal fines imposed by the panel of judges are subsidair or can be replaced with confinement bodies. The problem of this research is formulated: how is the practice of the execution of criminal fines against the prepetrators of excise crime, namely the sale of goods without the marking of excise payment. The approach used is normative juridicial and empirical juridicial. Data were collected through literature studies and field studies, then analyzed qualitatively.  In accordance with the description of the results of the study shows that: The practice of the execution of fines against the perpetrators of excise criminal acts, namely the sale of goods without the marking of excise payment carried out by the Bandar Lampung District Attorney after receiving a copy of the court's decision from the Registrar no later than one week after the verdict was read.  Furthermore, the Head of the Bandar Lampung District Prosecutor's Office issued a Court Decision Execution Order ordering the Prosecutors Team to execute a criminal fine against a convicted tax officer. The results of the execution are then compiled and reported in the Minutes of the Execution of Court Decisions.